Understanding the role of photoprotection in disease resistance to Septoria Tritici Blotch in wheat - Angelopoulou, Dimitra (2022)
Zymoseptoria tritici, a fungal pathogen of wheat and the causal agent of Septoria Tritici Blotch (STB), is a particular challenge to wheat production on a global level, causing severe crop losses. As the site of photosynthesis, the chloroplast plays a crucial role in energy balance and trade-off between growth demands and response to environmental stresses and it is gaining an ever-growing attention due to its multilayered involvement in disease response and downstream signalling. However, very little is known regarding wheat resistance responses to Z. tritici and the involvement of chloroplastic photoprotection. In the following thesis, I present data indicating the importance of photoprotection, through non-photochemical quenching (NPQ), in disease resistance of wheat plants against virulent and avirulent Z. tritici isolates.